Forest fragmentation reduces seed dispersal of Duckeodendron cestroides, a Central Amazon endemic - Cramer, Jennifer M.; Mesquita, Rita de Cássia Guimarães; Bentos, Tony Vizcarra; Moser, Barry; Williamson, G. Bruce (Biotropica, 2007)
Fragmentation that alters mutualistic relationships between plants and frugivorous animals may reduce the seed dispersal of trees. We examined the effects of forest fragmentation on the distributions of seeds and seedlings of a Central Amazon endemic tree, Duckeodendron cestroides. In the dry seasons of 2002-2004, seeds and first-year seedlings were counted within wedge-shaped transects centered around Duckeodendron adults in fragments and nearby continuous forests at the Biological Dynamics of Forest Fragmentation Project. Analyses showed that fragmentation reduced seed dispersal quantity and quality. The percent and distance of dispersed seeds were both twice as great in continuous forest as in fragments. The distances of each tree's five furthest dispersed seeds were three times greater in continuous forest than fragments. Over the 3-yr study, 20 times more seeds were dispersed more than 10 m from parent crowns in continuous forest than fragments. A regression analysis showed more dispersed seeds at all distances in continuous forest than fragments. Dispersal differences were strong in 2002 and 2004, years of large fruit crops, but weak or absent in 2003, when fruit production was low. As distance from parent crowns increased, the number of seedlings declined more rapidly in fragments than continuous forest. Distance-dependent mortality between the seed and seedling stages appeared to be more important in continuous forest than fragments. This research provides ample, indirect evidence demonstrating that forest fragmentation can result in the breakdown of a seed dispersal mutualism, potentially jeopardizing the reproduction of a rare, tropical tree. © 2007 The Author(s).
Keywords: Endemic Species; Forest Ecosystem; Fruit Production; Habitat Fragmentation; Mutualism; Regression Analysis; Seed Dispersal; Shrub; Animalsia; Duckeodendron; Duckeodendron Cestroides